ENGLISH STUDY PADA MAHASISWA PROGRAM STUDI S1 KEBIDANAN UNIVERSITAS SARI MULIA BANJARMASIN - Vebruati, Vebruati; Januarsih, Januarsih; Ahmad Rizani, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
This study is aimed at identifying and analyzing the needs of ESP learning material in learning English at diploma midwifery students. To find out the correct reference, needs analysis is urged to be done to obtain information about what the students really need to support their learning process at the present time or in the future career. This study was conducted by using qualitative approach and descriptive method. The samples were students from Midwifery Study Program of Sari Mulia University Banjarmasin who are currently taking English subject and the sampling technique used was purposive random sampling. Meanwhile, a questionnaire as the instrument for this study was arranged in closed-ended form. The data analysis was descriptive analysis in the form of number and percentage. The study revealed that the needs of nursing students on English subject are very diverse and it can be concluded that they need English not only for their current needs as they can communicate in English to support their education in nursing field, but also for their future professional career. Therefore, it is recommended that ESP English teachers or other related parties should accommodate the needs of these students. In addition, it is suggested to always conduct needs analysis since the needs of ESP learners are constantly changing